Residue Mutations in Murine Herpesvirus 68 Immunomodulatory Protein M3 Reveal Specific Modulation of Chemokine Binding - Šebová, Radka; Bauerová-Hlinková, Vladena; Beck, Konrad; Nemčovičová, Ivana; Bauer, Jacob; Kúdelová, Marcela (Frontiers in Cellular and Infection Microbiology, 2019)
The M3 protein encoded by murine gammaherpesvirus 68 (MHV-68) is a unique viral immunomodulator with a high-affinity for a broad spectrum of chemokines, key mediators responsible for the migration of immune cells to sites of inflammation. M3 is currently being studied as a very attractive and desirable tool for blocking the chemokine signalling involved in some inflammatory diseases and cancers. In this study, we elucidated the role of M3 residues E70 and T272 in binding to chemokines by examining the effects of the E70A and T272G mutations on the ability of recombinant M3 protein, prepared in Escherichia coli cells, to bind the human chemokines CCL5 and CXCL8. We found that the E70A mutation enhanced binding of M3 to CCL5 by about two times but had little effect on its binding to CXCL8. In contrast, the T272G mutation was found to be important for thermal stability of M3 and significantly decreased M3’s binding to both CCL5 (by about 4×) and CXCL8 (by about 5×). We also constructed in silico models of the wild-type M3–CCL5 and M3–CCL8 complexes and found substantial differences in their physical and chemical properties. Models of the E70A and T272G M3 mutants suggested the roles of these two residues in chemokine binding. In sum, we have confirmed that site-directed mutagenesis could be an effective tool for modulating the blockade of particular chemokines by M3, as desired in therapeutic treatments for severe inflammatory illnesses arising from chemokine network dysregulation.